Digital Transformation Strategy For PT Penjaminan Infrastruktur Indonesia (PERSERO) - Yunan Novaris Arifidianto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
PT Penjaminan Infrastruktur Indonesia (Persero)/Indonesia Infrastructure Guarantee Fund (IIGF) is very aware of the important role of digital technology in collaborating both with internal and external stakeholders. The use of digital technology effectively will speed up the process of collaboration both within IIGF and expanded by digital collaboration with external stakeholders. In this final project will explore how to develop a digital transformation strategy at IIGF by studying literature on digital innovation theories, digital transformation, business model transformation, business process transformation and cultural/organizational transformation. The research method in this final project by identifying business issues, analyzing the status quo with interviews, analyzing factors related to digital transformation, formulating effective digital transformation strategies and providing recommendations for business solutions that can be pursued by the management of IIGF, implementation plan of digital transformation more effective. Based on the findings in this study, the results are that we provide business solutions within 3 main elements in digital transformation, namely people, processes and technology. Keywords: Indonesia Infrastructure Guarantee Fund, PT PII (Persero), Government Guarantee, PPP, Digital Transformation Strategy